Experiences from conducting a registered report as an early career researcher. (September 2021) - Puhlmann, Lara; Linz, Roman
Abstract : Registered reports (RR) are an effective tool not just for combating the replication crisis but also for increasing transparency and methodological rigor in life sciences. Since their conception in 2013, there has been an exponential growth in the adoption of RR by journals and the scientific community. At the same time, expertise with this new publishing format is slim and many researchers do not know what to expect when conducting a RR, which can impede implementation. In this presentation, I share my experiences with a secondary RR we recently conducted in the field of psychoneuroendocrinology. Previous research associated lower peripheral levels of brain-derived neurotrophic factor (BDNF), a prominent neurotrophin involved in adult synaptic plasticity, with smaller hippocampal volumes in patient and aging populations. We investigated whether this association would also be also observable in younger, healthy adults. I describe the complete process of conducting this research in the context of a RR. In doing so, I address common questions, such as how to handle divergence from the peer-reviewed study protocol and to what extent data exploration is possible in this format. Finally, I share some insights including possible advantages and challenges of conducting a RR, with a particular emphasis on the early career researcher perspective. These points and subsequent discussion may aid researchers in deciding whether to pursue their own research questions in the form of a RR.